Nanometer Scale Surface Protein Patterns for Spatially Controlled Cell Adhesion - Vurmaz, D.; Pesen Okvur, Devrim; Oyman, G.; Heinz, W. F.; Werbin, J. L.; Hoh, J. H.; Haviland, D. B.; Okvur, D. Pesen (American Society for Cell Biology, 2012)
[No abstract available]